2011
DOI: 10.1097/hjh.0b013e32833ea821
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous ouabain and the renin–angiotensin–aldosterone system: distinct effects on Na handling and blood pressure in human hypertension

Abstract: Objective To evaluate whether the renin–angiotensin–aldosterone system (RAAS) and endogenous ouabain system differently affect renal Na handling and blood pressure. Methods Three hundred and one patients in whom we compared blood pressure, and renal Na tubular reabsorption in the basal condition and 2 h (T120) after saline infusion. Results Following multivariate-adjusted linear and quartiles analysis, baseline mean blood pressure (MBP) was significantly higher (113.7 ± 1.33 mmHg) in the fourth versus the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 29 publications
(43 reference statements)
1
24
0
2
Order By: Relevance
“…28 Furthermore, plasma EO levels were reported to be higher in the offspring of families with a positive history of hypertension than in subjects with no such family history, to correlate with blood pressure levels, and relate to some indices of diastolic left ventricular structure and function. 29 Whereas review articles in several high-profile journals, often but not uniquely from the University of Maryland and Milan workers, have taken for granted that EO exists and is of pathophysiological importance, 24,25,[29][30][31][32] questions have been raised by us and several other research groups. At an Endocrine Society meeting in 1995, opinions were divided as to whether authentic ouabain circulates in human plasma and is of adrenocortical origin.…”
mentioning
confidence: 99%
“…28 Furthermore, plasma EO levels were reported to be higher in the offspring of families with a positive history of hypertension than in subjects with no such family history, to correlate with blood pressure levels, and relate to some indices of diastolic left ventricular structure and function. 29 Whereas review articles in several high-profile journals, often but not uniquely from the University of Maryland and Milan workers, have taken for granted that EO exists and is of pathophysiological importance, 24,25,[29][30][31][32] questions have been raised by us and several other research groups. At an Endocrine Society meeting in 1995, opinions were divided as to whether authentic ouabain circulates in human plasma and is of adrenocortical origin.…”
mentioning
confidence: 99%
“…Moreover, exposure of primary cultured rodent arterial myocytes to nanomolar ouabain for 48 -72 h also increases expression of NCX1 and TRPC6 proteins (49). In this context, it is noteworthy that plasma EO levels are significantly elevated in several rodent hypertension models (15,16,29), as well as in 40 -50% of humans with essential hypertension and in most patients with aldosterone-linked hypertension (40,43,51). We suggested that the increased peripheral vascular resistance in the rodent hypertension models results, in part, from the augmented Ca 2ϩ signaling and vasoconstriction as a consequence of the Ca 2ϩ transporter upregulation in the arterial myocytes (7,34).…”
Section: Effects Of Prolonged Ouabain Treatment On Arterial Myocytes mentioning
confidence: 98%
“…The main conclusion from these studies is that the same ouabain-dependent long-term mechanisms that augment Ca 2ϩ signaling and vascular tone in rodent arterial myocytes (49) are also functional in human arterial myocytes. The implication is that in human hypertension, including a large fraction of patients with essential hypertension and those with hypermineralocorticoid syndromes, in whom plasma EO is elevated (40,43,51), these Na ϩ and Ca 2ϩ transport mechanisms promote the increased vascular tone. They also augment responses to (enhanced) sympathetic drive and to humoral vasoconstrictors and, thereby, elevate BP.…”
Section: A B C D Ementioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged ouabain infusion in rats causes an increase in plasma creatinine, blood pressure and tubular Na reabsorption. [7], Recently [14], we have shown the relationship between EO and impaired glomerular filtration rate as direct consequence of long exposure to increased level of plasma EO in hypertensives. Therefore, we conducted these prospective observational studies to test the time course of circulating EO changes during cardio pulmonary bypass (CPB), where acute volume and blood pressure modification occurs.…”
Section: Introductionmentioning
confidence: 94%